Amphiphilic galactosylated phthalocyanines - Kumru, Ufuk; Ermeydan, Mahmut Ali; Dumoulin, Fabienne; Ahsen, Vefa (World Sci Publ Co Inc, 2008)
Two amphiphilic Ni phthalocyanines bearing a hydrophilic galactose head facing six hydrophobic thiohexyl chains are described. The place of the glycosylation step on the overall synthetic pathway is discussed. For the first time, phthalocyanines are used as acceptors in glycosylation reactions, in excellent yields. Copyright (C) 2009 Society of Porphyrins & Phthalocyanines.
Keywords: galactosylated phthalocyanine; glycosylation acceptor; amphiphilicity